2011
DOI: 10.1007/s11302-010-9212-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors

Abstract: There is evidence that gonadal hormones may affect the perception of painful stimulation, although the underlying mechanisms remain unclear. This investigation was undertaken to determine whether the adenosine 5′-triphosphate (ATP) receptor subunit, P2X 3 , is involved in the modulatory action of estrogen in peripheral pain signal transduction in dorsal root ganglion (DRG). The mechanical pain behavior test, real-time quantitative reverse transcription-polymerase chain reaction analysis, and Western blot metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…Our results show that the expression of P2X3R in neurons was significantly increased in CFA-treated rat [44] and in TNBS-induced colitis in rats [23,25], indicating a vital role of P2X3R in inflammatory reactions. It has been reported that estrogen replacement decreased P2X3 upregulation in DRG after ovariectomy [30]. In the present study, estrogen replacement significantly decreased peripheral pain sensitivity and P2X3R expression in DRG from CFA-treated OVX rats.…”
Section: Estrogen Modulates P2x3r Via Erβ In Inflammatory Painsupporting
confidence: 66%
See 3 more Smart Citations
“…Our results show that the expression of P2X3R in neurons was significantly increased in CFA-treated rat [44] and in TNBS-induced colitis in rats [23,25], indicating a vital role of P2X3R in inflammatory reactions. It has been reported that estrogen replacement decreased P2X3 upregulation in DRG after ovariectomy [30]. In the present study, estrogen replacement significantly decreased peripheral pain sensitivity and P2X3R expression in DRG from CFA-treated OVX rats.…”
Section: Estrogen Modulates P2x3r Via Erβ In Inflammatory Painsupporting
confidence: 66%
“…Our previous study has shown that both P2X3 expression and functions could be affected by estrogen [28][29][30][31], while the effect of ERβ activation on P2X3R in colitis is unknown. In the present study, injection of DPN (10 μg) for 4 days decreased P2X3R protein expression in colitis.…”
Section: Involvement Of P2x3 Receptors In Tnbs-induced Colitis Ratsmentioning
confidence: 98%
See 2 more Smart Citations
“…The use of the estrogen receptor antagonist, ICI 182,780, blocked the reduction in the receptor subunit protein level. Thus, 17β-estradiol participates in the control of peripheral pain signal transduction by modulating the expression of the P2X 3 subunit and, consequently, P2X 3 receptormediated events [114]. On the other hand, P2X 3 receptor mRNA was significantly decreased in DRG neurons of ovariectomized rats.…”
Section: P2 Receptors and Steroid Hormone Receptorsmentioning
confidence: 95%